2016
DOI: 10.1103/physreve.93.052229
|View full text |Cite
|
Sign up to set email alerts
|

Renormalized time scale for anticipating and lagging synchronization

Abstract: We consider fluctuations of the dissipated energy in nonlinear driven diffusive systems subject to bulk dissipation and boundary driving. With this aim, we extend the recently-introduced macroscopic fluctuation theory to nonlinear driven dissipative media, starting from the fluctuating hydrodynamic equations describing the system mesoscopic evolution. Interestingly, the action associated to a path in mesoscopic phase-space, from which large-deviation functions for macroscopic observables can be derived, has th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 51 publications
(135 reference statements)
4
12
0
Order By: Relevance
“…In the presence of transmission delays, anticipated synchronization [9][10][11][12][13][14] is another remarkable collective behaviour that is observed in monkeys performing visual discrimination tasks. 6,7 Multi-electrode recordings showed a dominant directional influence between areas of sensorimotor cortex (as assessed by Granger causality), accompanied by either a negative or a positive phase lag between them.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In the presence of transmission delays, anticipated synchronization [9][10][11][12][13][14] is another remarkable collective behaviour that is observed in monkeys performing visual discrimination tasks. 6,7 Multi-electrode recordings showed a dominant directional influence between areas of sensorimotor cortex (as assessed by Granger causality), accompanied by either a negative or a positive phase lag between them.…”
Section: Introductionmentioning
confidence: 89%
“…Indeed, an inspection shows that the spectrum of A þ B has only negative real part as long as 2K À K 0 > 0: (19) Hence, Eqs. (14) and (19) provide the conditions for anticipated synchronization in the small-d limit.…”
Section: Stability Of Phase-lockingmentioning
confidence: 99%
“…f (S) is a vector function that describes the autonomous dynamical system, K is the coupling matrix and the delayed term R(t−t d ) is the self-feedback [13]. The solution R(t) = S(t + t d ), characterizes the anticipated synchronization and has been verified in a variety of theoretical [13][14][15][16][17][18][19] and experimental [20][21][22] studies. The striking aspect of this solution is that in a time t the Receiver R predicts the state of the Sender S in a future time…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous work on anticipated synchronization in the framework of Equation (1) (Pyragienè and Pyragas, 2013; Hayashi et al, 2016; Dima et al, 2018), we studied the effect that an inhibitory connection and the external current plays in determining the frequency of the receiver system when the sender and the receiver are uncoupled (the receiver free-running frequency ω R ). In fact, we find that both the inhibitory conductance and the external stimuli modify the receiver internal dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…AS has also been reported in a chain consisting of a sender and two receivers with switching parameters (Pyragienè and Pyragas, 2015), between two Hodgkin-Huxley neurons with different depolarization parameters (Simonov et al, 2014) and in the presence of an inhibitory loop mediated by an interneuron with a free-running frequency greater than the others (Matias et al, 2017). It has also been shown that AS may appear between two neuron models directly coupled provided that the mean frequency of the free receiver is greater than the mean frequency of the sender with (Hayashi et al, 2016) and without the explicit time-delay (Pyragienè and Pyragas, 2013; Dima et al, 2018). AS has been verified in a system in which the delayed feedback has been replaced by a simple, low-order all-pass filter (Pyragiene and Pyragas, 2017).…”
Section: Introductionmentioning
confidence: 99%